Textbook of medical biochemistry - Chatterjea M N; Shinde, Rana (New Delhi Jaypee brothers medical publishers, 2023)
"A fully revised and updated text. Written in simple and lucid language as per the MCI syllabus. Presents an intelligent and comprehensive study. Enriched with relevant subject information of medical biochemistry. Covers basics of biochemistry with clinical approach. Highlights important portions like clinical aspects/significance for better understanding. Provides colour photographs to make the book more attractive. Includes MCQs, essay and short type questions at the end of each chapter to help the students for examination. Covers all the topics of current interests for the undergraduate and postgraduate students, teachers, and biochemists."
Keywords: Medical Biochemistry